Does vitamin D level associate with pregnancy outcomes in Chinese women undergoing in vitro fertilization/intracytoplasmic sperm injection‐embryo transfer? A retrospective cohort study. Issue 3 (19th December 2022) - Yu, Zhengchen; Sun, Yiqun; Wang, Peng; Hu, Yinkai; Zhou, Yuxi; Xie, Jinrui; Lu, Zhenzhen; Xu, Luxuan; Zhao, Junzhao; Chi, Haihong
Abstract: Aim: To explore the relationship between serum 25(OH)D level and pregnancy outcomes (clinical pregnancy rate [CPR] and live birth rate [LBR]) in Chinese women receiving in vitro fertilization (IVF)/intracytoplasmic sperm injection (ICSI)‐embryo transfer (ET) (IVF/ICSI‐ET). Methods: A total of 612 patients included in the study were divided into four cohorts according to serum 25(OH)D with the threshold of 20 ng/ml, 25 ng/ml, 30 ng/ml, and retrospectively analyzed. Results: None of the baseline characteristics of participants was significantly different in the four cohorts except gravid status. The trend of 25(OH)D concentration was positively correlated with CPR and LBR. The younger (age: p < 0.001 both in CPR and LBR) women with primary infertility (infertility type: p = 0.004 in LBR) were more likely to get a better pregnancy outcome under the same 25(OH)D concentration stages . As shown on heatmap plots, CPR, and LBR were significantly increased for 25(OH)D concentrations above 30.00 ng/ml and women younger than 30 years old. The adjusted binary logistic regression and restricted cubic spline (RCS) showed that there existed a nonlinear positive correlation between 25(OH)D concentration and pregnancy outcome (CPR and LBR) ( P nonlinear < 0.001, respectively). The women with a sufficient 25(OH)D concentration (30 ng/ml) had 1.07 (clinical pregnancy) and 1.05 (live birth) times higher successful birth outcomes compared to women with an insufficient 25(OH)D concentration (25 ng/ml). (OR25 ng/ml, ref = 30 ng/ml [95% CI] = 0.935 [0.932–0.938] and 0.947 [0.945–0.950], p < 0.001, respectively). Conclusion: In Chinese women receiving IVF/ICSI‐ET, the serum level of 25(OH)D demonstrated a nonlinear positive correlation with pregnancy outcomes (CPR and LBR), with stronger correlations above 25 ng/ml and worse yields below 30 ng/ml. However, it could not yet be considered different in distinct ages.